2014
DOI: 10.1177/0961203313520059
|View full text |Cite
|
Sign up to set email alerts
|

An SLE patient with prolactinoma and recurrent granulomatous mastitis successfully treated with hydroxychloroquine and bromocriptine

Abstract: Granulomatous mastitis (GM) is a rare benign mammary lesion in which autoimmunity and hyperprolactinemia are considered possible etiological factors. GM has a high frequency of relapse and may lead to chronic ulceration and fistula if not treated properly. Here we report a case of a 22-year-old systemic lupus erythematosus (SLE) patient with three years' disease duration, stable on prednisone and hydroxychloroquine, who was found to have prolactinoma and recurrent GM after she discontinued medication on her ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Recently, prolactinoma and recurrent granulomatous mastitis in SLE patients have been successfully treated with hydroxychloroquine. 19 In patients with CLE, a combination of hydroxychloroquine and quinacrine is more appropriate as initiation therapy than hydroxychloroquine or chloroquine monotherapy and improves the Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI) score and the response rate in non-responders. 20 , 21 Hydroxychloroquine is beneficial for patients with membranous lupus nephritis.…”
Section: Indications For Chloroquine Analoguesmentioning
confidence: 99%
“…Recently, prolactinoma and recurrent granulomatous mastitis in SLE patients have been successfully treated with hydroxychloroquine. 19 In patients with CLE, a combination of hydroxychloroquine and quinacrine is more appropriate as initiation therapy than hydroxychloroquine or chloroquine monotherapy and improves the Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI) score and the response rate in non-responders. 20 , 21 Hydroxychloroquine is beneficial for patients with membranous lupus nephritis.…”
Section: Indications For Chloroquine Analoguesmentioning
confidence: 99%
“…Non-surgical recommendations include pharmacologic (i.e., steroids, methotrexate, azathioprine, tuberculosis medications) or close observation [1,3,6,17] . A recent case report in a patient with systemic lupus erythematosus (SLE) and prolactinoma found that treatment of both conditions (immunosuppressive therapy for SLE and bromocriptine for prolactinoma) were necessary to maintain remission of IGM [18] . In the largest series to date, Pandey, et al reported that 23% of 49 IGM patients had recurrence after corticosteroid treatment [1] .…”
Section: Discussionmentioning
confidence: 99%
“…These changes IL [ 7 , [24] , [25] , [27] , [28] ]. As reported by Saydam et al the significant differences in IL-22 and −23 levels between GM patients and the control group were thought to contribute to autoimmunity in GM pathogenesis [ 28 ] in addition, it is been reported that rheumatoid factor (RF), ANA, and anti-dsDNA antibodies were positive in all patients with GM without other clinical manifestations suggestive of autoimmune [ [31] , [34] ].…”
Section: Pathophysiologymentioning
confidence: 98%